Coronary angiography findings in patients with refractory vs. non-refractory ventricular fibrillation cardiac arrest. (25th November 2020) - Nas, J; Thannhauser, J; Damen Van Dijk, E.G.J.A; Verkroost, C; Van Wely, M; Van Geuns, R.J; Van Royen, N; Bonnes, J.L; Ten Cate, T; Brouwer, M.A
Abstract: Introduction: Refractory ventricular fibrillation (VF) is usually defined as the need for >3 shocks and poses a therapeutic challenge during cardiac arrest. For these patients, new treatment strategies such as early invasive management are under active investigation, yet the underlying myocardial substrate has poorly been characterised. In search of potential therapeutic targets, we studied coronary angiography findings in refractory vs. non-refractory VF. Methods: Out of our prospective cardiac arrest registry (2013–2018), we studied all VF-patients that were transported to our tertiary hospital, and underwent coronary angiography (CAG). CAGs were assessed by interventional cardiologists blinded for clinical outcomes and patient category, being either patients with refractory (>3 shocks) or non-refractory VF (≤3 shocks). CAG images were scored using predefined data-sheets with uniform definitions. Results: We studied 301 patients, of which the majority was male (82%) and median age was 63 (53–70) years. Of all patients, 105 (35%) had refractory VF and 196 (66%) had non-refractory VF. We found no differences in baseline and arrest characteristics (i.e. arrest location, witnessed arrest, bystander CPR, EMS response time and AED use) between refractory and non-refractory VF. In both groups, significant coronary artery disease (≥1 stenosis >70%) was highly prevalent (78 vs. 77%, p=0.76). Acute coronary occlusions were more prevalent in the refractory VF group (41% in refractory VF vs. 26% in non-refractory VF, p=0.006). Figure 1 demonstrates that the proportion patients with an coronary occlusion increases with an increasing number of shocks (p for trend=0.003). Chronic total occlusions did not differ between both groups (29% vs. 33%, p=0.47). Refractory VF-patients had lower proportions 24-hour survival (75% vs. 93%, p<0.001) and survival to discharge (61% vs. 78%, p=0.002). Conclusion: In this VF-cardiac arrest study on patients transported to the hospital and undergoing coronary angiography, acute coronary occlusions were more prevalent in refractory compared to non-refractory VF. After confirmation of these findings, further studies on the potential benefit of early treatment of acute coronary occlusions in patients with refractory VF are eagerly awaited. Funding Acknowledgement: Type of funding source: None